Pemanfaatan Limbah Sekam Sebagai Bahan Media Tanam di Desa Ciamis Kecamatan Sungkai Utara Kabupaten Lampung Utara - Lestari, Sri Puji; Ahmal, Vicko Javier; Alahsyari, Muhammad Fauzi; Rika; Setiawan, Agus; Azzam, Muhammad Abdullah; Hidayatullah, Bayu (Pengabdian Kepada Masyarakat Cendekia, 2025)
Community Service (KKN) is an educational approach that offers students actual experience by immersing them in society beyond the school, thereby instructing them on how to detect social issues affecting the community. Community service will explicitly demonstrate the correlation between the educational sphere and its societal advantages. The undertaken activity involves the production of rice husk charcoal, which serves as a planting medium. Rice husk is an agricultural byproduct, constituting the outermost layer of rice grains generated during the milling process. Rice plants are among the commodities cultivated in Ciamis Village. Rice milling byproducts, specifically rice husks, can serve multiple functions such as raw materials for animal feed, growth substrates, and alternative energy sources. The Ciamis Village community's ignorance about the advantages of rice husks results in suboptimal utilisation of rice husks derived from rice milling waste. Generally, individuals utilise rice husks as supplementary animal feed, particularly for poultry. The objective of this rice husk charcoal production initiative is to disseminate knowledge regarding the utilisation of agricultural waste, specifically rice husks, as a planting medium. The activity's implementation indicates that the village apparatus positively embraced the use of rice husk charcoal waste, as they supported students by supplying raw materials, specifically rice husks, and providing land for the application of rice husk charcoal in raised beds. In the long term, the use of rice husk charcoal as a planting medium is anticipated to enhance food security for the inhabitants of Ciamis Village.